International Equity Portfolios and Currency Hedging: The Viewpoint of German and Hungarian Investors - Gyöngyi Bugár; Raimond Maurer (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2001)
In this paper we study the benefits derived from international diversification of stock portfolios from German and Hungarian point of view. In contrast to the German capital market, which is one of the largest in the world, the Hungarian Stock Exchange is an emerging market. The Hungarian stock market is highly volatile, high returns are often accompanied by extremely large risk. Therefore, there is a good potential for Hungarian investors to realize substantial benefits in terms of risk reduction by creating multi-currency portfolios. The paper gives evidence on the above me ntioned benefits for both countries by examining the performance of several ex ante portfolio strategies. In order to control the currency risk, different types of hedging approaches are implemented.
urn:nbn:de:hebis:30-18249
Keywords: 330; International Portfolio Diversification; Estimation Risk; Hedging the Currency Risk; Emerging Stock Markets; Portfolio-Management; International; Portfolio-Investition; Währungsmanagement; Internationaler Finanzmarkt; Risiko; Hedging; Deutschland; Ungarn